DL-Shuttle : Badminton Coaching Training Assistance System Using Deep Learning Approach - Chai, Zi Jian; Johari, Abdullah; Halikul, Lenando (IEEE, 2022)
Coaching in sports is a process that focuses on improving the performance of players by providing them guidance and training. Players that are usually involve in the coaching are those professional players or players that target to be involved in competitive environment. One of the sports that have the most coaches to train players in Malaysia is badminton. Since Datuk Lee Chong Wei announced his retirement from the Malaysia badminton national team, more and more players start to look forward to becoming the next hero for Malaysia. Therefore, there is a sudden growth of demand for badminton coaches in Malaysia, leading to a rise in the cost of hiring a coach. A lot of beginners do not afford to hire a coach as it is expensive. Furthermore, in this period of pandemic, it is better to avoid meeting with one another to reduce the risk of getting Covid-19. Therefore, this project was intended to design and develop a badminton coaching assistance system using deep learning which allowed users to train on their own without physically meeting with coaches. This system become a personal coach for players to undergo their training. It can be used in any place with badminton court and without the need to schedule for human coach. The deep learning approach and the system produced is able to produce above 80% accuracy in detection selected training pose.